2018
DOI: 10.5114/reum.2018.76903
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of state and trait anxiety as moderated by perceived social support among Nigerian patients with rheumatoid arthritis

Abstract: ObjectivesTo assess the levels of state and trait anxiety and determine their relationships with perceived social support among Nigerian patients with rheumatoid arthritis (RA).Material and methodsA cross-sectional study of 50 patients satisfying the 2010 American College of Rheumatology/European League against Rheumatism Classification Criteria for RA was conducted. Anxiety was assessed using the Spielberger State-Trait Anxiety Inventory (STAI), perceived social support by the Interpersonal Support Evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…Consistent with prior findings, previous mental illness [49], non-heterosexuality [10,11] and intimate partner violence [8,13] were individually associated with higher anxiety and depressive symptoms while perceived social support was associated with lower anxiety and depressive symptoms [18,50]. Together, these variables explained the largest proportion of variance in both anxiety and depressive symptoms with intimate partner violence and perceived social support retaining independent associations with both symptoms.…”
Section: Associations With Anxiety and Depressive Symptomssupporting
confidence: 84%
“…Consistent with prior findings, previous mental illness [49], non-heterosexuality [10,11] and intimate partner violence [8,13] were individually associated with higher anxiety and depressive symptoms while perceived social support was associated with lower anxiety and depressive symptoms [18,50]. Together, these variables explained the largest proportion of variance in both anxiety and depressive symptoms with intimate partner violence and perceived social support retaining independent associations with both symptoms.…”
Section: Associations With Anxiety and Depressive Symptomssupporting
confidence: 84%
“…A multinational study which examined the association between social support and mental wellbeing among adolescents reported that increased perception of social support from a caring family member or significant others negatively correlated with the severity of depressive symptoms (Cheng et al, 2014). Apart from the adolescent population, the importance and influence of social support have been described among diverse populations such as caregivers of patients with oncological disorders (Dębska, Pasek, & Wojtyna, 2017), individuals with sudden loss of auditory function (Hricová, 2018), patients receiving treatment for rheumatoid arthritis (Akintayo et al, 2018) and nursing students (Zarzycka, Ślusarska, Dyk, Bednarek, & Trojanowska, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Spielberger State-Trait Anxiety Inventory (STAI) was used to assess the degree of anxiety with 2 subscales as state anxiety (STAI-S) and trait anxiety (STAI-T) (17). The statements in the inventory are rated from 1 to 4 according to how much of each item the individual is currently feeling (STAI-S) or how often each item is felt (STAI-T).…”
Section: Measurement Of Anxiety: the Spielberger State-trait Anxiety ...mentioning
confidence: 99%
“…The statements in the inventory are rated from 1 to 4 according to how much of each item the individual is currently feeling (STAI-S) or how often each item is felt (STAI-T). The total scores range from 20, which reflects the lowest possible degree of anxiety (state or trait), to 80, the highest possible anxiety score (17).…”
Section: Measurement Of Anxiety: the Spielberger State-trait Anxiety ...mentioning
confidence: 99%